Phytochemical and biological studies on rare and endangered plants endemic to China. Part XV. Structurally diverse diterpenoids and sesquiterpenoids from the vulnerable conifer Pseudotsuga sinensis. (January 2020) - Huang, Ting; Ying, Sheng-Hui; Li, Jing-Ya; Chen, Hao-Wei; Zang, Yi; Wang, Wen-Xuan; Li, Jia; Xiong, Juan; Hu, Jin-Feng
Abstract: An extensive phytochemical investigation on the chemical constituents from the needles and twigs of the vulnerable conifer Pseudotsuga sinensis yielded 19 diterpenoids and 21 sesquiterpenoids with various carbocyclic skeletons. Among them, 13 (named pseudosinins A–M, resp.) were undescribed compounds. Their structures with absolute configurations were characterized by a combination of spectroscopic methods, calculated and experimental electronic circular dichroism (ECD) data, quantum chemical calculations of the chemical shifts, and single crystal X-ray diffraction analyses. In particular, an array of labdane-derived norditerpenoids with C19 -, C18 -, and C16 -skeletons, and related drimane-type sesquitepenoids with C15 - and C13 -skeletons were found in the title plant. The possible biogenetic relationships of these degraded terpenoids were briefly discussed. Among the isolates, pseudosinin D, cis -communic acid, and 4 β, 15-dihydroxy-19-norabieta-8, 11, 13-trien-7-one showed moderate inhibitory activities against the enzyme ATP-citrate lyase (ACL), a potential drug target for the treatment of hyperlipidemia and hypercholesterolemia. Graphical abstract: Forty di- and sesqui-terpenoids with various carbocyclic frameworks, including thirteen undescribed ones, were isolated and characterized from the vulnerable conifer Pseudotsuga sinensis . In particular, a series of labdane-derived degraded terpenoids with C19 -/C18 -/C16 -/C15 -/C13 -skeletons were encountered. Three isolates showed considerable inhibition on the enzyme ATP-citrate lyase (ACL). Image 1 Highlights: An extensive phytochemical study on the vulnerable Pseudotsuga sinensis was reported. Thirteen undescribed di- and sesqui-terpenoids (pseudosinins A–M) were identified. The biosynthetic pathways of the labdane-derived degraded terpenoids were proposed. Three isolated diterpenoids showed considerable inhibitory activities against ACL.